Valuation Effect of Corporate Name Change in Chinese Technology Stocks - Li Hui; Tan Yeng May (Asian Academy of Management Journal of Accounting and Finance, 2022)
Each year, hundreds of firms change names in China. A corporate name change is an expensive proposition. Hence, one may wonder whether investors truly reward such corporate actions. This study examines the short-term valuation effect of corporate name changes for China technology stocks. We classify the nature of name changes into the concept vs. non-concept related name changes and strategic vs. cosmetic name changes. In addition to the nature of name change, we also examine the effect of market sentiment on the name change of technology companies’ values. Our findings reveal that firms with concept-related name changes and strategic name changes generate significantly positive cumulative abnormal returns on the announcement date. However, the same outcome cannot be achieved in the pre- and post-event periods. Our results further show that investors of Chinese tech stocks are not influenced by their sentiment, suggesting that investors are bounded rational in China.